2017
DOI: 10.1016/j.oraloncology.2016.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the management of radiotherapy-induced xerostomia and hyposalivation: A systematic review and meta-analysis

Abstract: Introduction: Salivary gland hypofunction is a common and permanent adverse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 38 publications
2
107
0
18
Order By: Relevance
“…В результате распада и выведения СЖ клеточных структур РЖ увеличивается ее вязкость, повышается кислотность (pH≤5), что приводит к потере железой способности секретировать слюну; снижается (≤0,2 мл/мин) [19] или резко угнетается слюноотделение, развивается ксеростомия (0,1-0,2 мл/мин) [20,21]. При воздействии дозы ионизирующего излучения >10 Гр отмечают проявления ксеростомии разной степени тяжести у всех пациентов со ЗНО ЧЛО [5,6,13,18,21]. При суммарной дозе облучения (СОД) более 30 Гр проявления ксеростомии считают уже необратимыми [10,22].…”
Section: влияние ионизирующего излучения на структуру и функцию сж паunclassified
“…В результате распада и выведения СЖ клеточных структур РЖ увеличивается ее вязкость, повышается кислотность (pH≤5), что приводит к потере железой способности секретировать слюну; снижается (≤0,2 мл/мин) [19] или резко угнетается слюноотделение, развивается ксеростомия (0,1-0,2 мл/мин) [20,21]. При воздействии дозы ионизирующего излучения >10 Гр отмечают проявления ксеростомии разной степени тяжести у всех пациентов со ЗНО ЧЛО [5,6,13,18,21]. При суммарной дозе облучения (СОД) более 30 Гр проявления ксеростомии считают уже необратимыми [10,22].…”
Section: влияние ионизирующего излучения на структуру и функцию сж паunclassified
“…Due to conflicting results their use is not recommended [11]. On the other hand, recent systematic review suggested that both pilocarpine and cevimeline can reduce xerostomia symptoms and increase salivary flow compared to placebo after RT but "some aspects of the relevant effect size, duration of the benefit, and clinical meaningfulness remain unclear" [65].…”
Section: Xerostomiamentioning
confidence: 99%
“…At present, available treatment modalities for mouth dryness include the following: altering the intake of xerogenic medication when possible; shifting the radiation field to protect the salivary glands in head and neck cancer patients [i.e., intensity-modulated radiation therapy (IMRT)] (Wang & Eisbruch, 2016); local application of saliva substitutes and stimulants; systemic intake of muscarinic agonists (sialogogues), such as pilocarpine and cevimeline (Aframian, Helcer, Livni, & Markitziu, 2006;Mercadante, Al Hamad, Lodi, Porter, & Fedele, 2017); and electrostimulation devices (Wolff et al, 2018). Since the prevalence of salivary gland impairment is relatively common (Ship et al, 2002), more cost-effective modalities are needed to overcome this morbidity.…”
mentioning
confidence: 99%